2019
DOI: 10.3389/fcell.2019.00062
|View full text |Cite
|
Sign up to set email alerts
|

The Social Component of Environmental Enrichment Is a Pro-neurogenic Stimulus in Adult c57BL6 Female Mice

Abstract: In rodents, the hippocampal dentate gyrus gives rise to newly generated dentate granule cells (DGCs) throughout life. This process, named adult hippocampal neurogenesis (AHN), converges in the functional integration of mature DGCs into the trisynaptic hippocampal circuit. Environmental enrichment (EE) is one of the most potent positive regulators of AHN. This paradigm includes the combination of three major stimulatory components, namely increased physical activity, constant cognitive stimulation, and higher s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 88 publications
(132 reference statements)
0
27
0
Order By: Relevance
“…Enriched environment enhances HC-mediated learning and plasticity (van Praag et al, 2000; Moreno-Jiménez et al, 2005; Baroncelli et al, 2010; Bergami et al, 2015; Alvarez et al, 2016; Moreno-Jimenez et al, 2019). A brief exposure of young-adult mice to EE was shown to promote new GC integration at an early developmental stage (second week), an effect mediated by the depolarizing action of GABAergic interneurons (Chancey et al, 2013; Alvarez et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Enriched environment enhances HC-mediated learning and plasticity (van Praag et al, 2000; Moreno-Jiménez et al, 2005; Baroncelli et al, 2010; Bergami et al, 2015; Alvarez et al, 2016; Moreno-Jimenez et al, 2019). A brief exposure of young-adult mice to EE was shown to promote new GC integration at an early developmental stage (second week), an effect mediated by the depolarizing action of GABAergic interneurons (Chancey et al, 2013; Alvarez et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The fact that both large and large+EE had similar effects on exploratory behaviors suggests that increased space and social complexity, in the absence of environmental enrichment, are sufficient to trigger an effect on motivated responses. Studies in female C57 mice showed similar results: just the social component of enriched environments could explain an increase in both non-social and social exploration time, which was correlated with an increased number of doublecortin expressing cells in the hippocampus, indicating increased neurogenesis (Moreno-Jiménez et al, 2019).…”
Section: Discussionmentioning
confidence: 68%
“…The efficacy of the EE protocol in reversing the short-and long-term memory deficit in young mice due to the lack of Adrβ3 could be explained by the findings of several previous studies showing that cognitive enrichment in rats contributes to better learning and the performance of declarative and procedural memory tasks. The increase in the dendritic tree in the third layer of the pyramidal neurons of the temporal lobe, changes in synaptic organization and an increase in the amount of intersections in both the basal and apical dendrites suggests a change in plasticity that involves neural reorganization and an increase in the number of neuronal contacts and the formation of a more complex neuronal network (33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%